Effects of the novel 2019 coronavirus outbreak (Covid-19) on the level of sports activities and mood of non-professional football players in Iran - Rezaei, S.; Aghababa, A.; Rohani, H.; Nabilpuor, M. (Journal of Organizational Behavioral Management in Sport Studies, 2021)
The aim of this study was to investigate the The effects of the new 2019 coronavirus outbreak (Covid-19) on the level of sports activities and mood of non-professional football players in Iran. This study is descriptive and a kind of field study. The statistical population of this study includes all male and female athletes who were played in non-professional football in the country before the Covid-19 era. For data collection, the standard questionnaire of the International Group of Covid-19 and Sport Researchers was used. The reliability of this questionnaire was determined by Cronbach's alpha method (R=0.82) and its validity was confirmed after review by a number of experts in this field. The mentioned questionnaire was published with the help of football delegations electronically and online and 686 questionnaires were completed and collected from all over the country in a random and stratified manner and were selected as a research sample. The results show that 84% of indoor places and 66.6% of open places are currently closed and 28.7% of people have lost their jobs due to the prevalence of Covid-19. Other results showed that there was a significant difference between the number of sessions and the intensity of training before the corona and during the corona; But there is no significant difference between the results of Covid-19 test and the degree of adherence to health laws and protocols. Conclusion that sports activities and mood are strongly influenced and reduced by Covid-19.